Phytochemical Characterization and Quantification of Phenolic, Flavonoid, and Tannin Contents in Ethanol Extract of Medicago sativa - Ramadhan, Majida; Faisal, Faisal; Nafisa, Nafisa; Mahyantika, Seftya Putri (Universitas Islam Indonesia, 2026)
Medicago sativa (alfalfa) leaves are known to contain diverse bioactive phytochemicals, particularly phenolic and flavonoid compounds that are commonly associated with antioxidant activity. This study aimed to characterize the phytochemical profile of the ethanol extract of alfalfa leaves and quantify its major phenolic constituents to provide chemical evidence supporting its antioxidant potential. Dried alfalfa leaves were extracted using maceration with ethanol 70%, followed by qualitative phytochemical screening, Fourier Transform Infrared (FTIR) analysis, and spectrophotometric determination of total phenolic, flavonoid, and tannin contents. Phytochemical screening confirmed the presence of alkaloids, phenolics, tannins, flavonoids, and triterpenoids, while saponins were not detected. Quantitative analysis showed that the extract contained a high total flavonoid content (136.25 ± 3.165 mg quercetin equivalents/g extract), along with appreciable levels of total phenolics (19.32 ± 0.814 mg gallic acid equivalents/g extract) and tannins (66.49 ± 0.927 mg tannic acid equivalents/g extract). These findings demonstrate that alfalfa leaf extract is a rich source of polyphenolic compounds, which are widely associated with antioxidant properties, thereby providing a scientific basis for further evaluation of antioxidant activity.